Status of Thyroid Function among Patients of National Medical College and Teaching Hospital - Budhathoki, Anup Shamsher; Gupta, Suprita; Sah, Sanjay Kumar; Sah, Navin Kumar; Sah, Navin Kumar; Yadav, Nirdhan; Patel, Amit Kumar; Ansari, Afroj; Pandey, Alan (Med Phoenix, 2020)
Background: Thyroid dysfunction is one of the most common endocrinopathies after Diabetes Mellitus. Thyroid dysfunction is defined as the alteration in Thyroid Stimulating Hormone (TSH) with normal or abnormal thyroid hormones. Nepalese population have a high risk for thyroid dysfunction with a high prevalence of iodine deficiency. Objective: To study the prevalence of thyroid dysfunction among the patients visiting National Medical College, Birgunj, Nepal for checkup and suggested to assess thyroid function. Materials and Methods: The hospital-based study was conducted in Central Laboratory, National Medical College and Teaching Hospital (NMCTH), Birgunj in collaboration with the Department of Biochemistry. Total 7040 patients visiting Central Laboratory for thyroid function assessment were included in the study between July 2017 to December 2019. The venous blood sample was collected and serum-free triiodothyronine(fT3), free tetraiodothyronine(fT4) and thyroid stimulating hormone (TSH) was estimated by Chemiluminescence Immunoassay (CLIA) method using Access 2 Beckman Coulter analyser. (Beckman Coulter Inc., California, USA). Results: Among 7040 subjects under study, 2138(30%) were found to have thyroid dysfunction with 13% having subclinical hypothyroidism, about 8% of overt hypothyroidism, about 4% with subclinical hyperthyroidism and 5% with overt hyperthyroidism. Majority of the thyroid dysfunction study group belonged to the 16-30 years age group followed by 31-45 years. Mean±SE for TSH, fT4 and fT3 levels show statistically significant differences in different thyroid disorders. Conclusion: The study revealed a high prevalence of subclinical hypothyroidism followed by overt hypothyroidism among the patients visiting National Medical College and Teaching Hospital, Birgunj, Nepal. A higher percentage of females were found to have thyroid dysfunction compared to male.